2020
DOI: 10.3389/fmicb.2020.01014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fermented Herbal Tea Residues on the Intestinal Microbiota Characteristics of Holstein Heifers Under Heat Stress

Abstract: Herbal tea residue (HTR) is a reusable resource with high nutritional value and bioactive substances content, which can be used as a feed additive. In the present study, HTRs were fermented by lactic acid bacteria, and then fed to a total of 90 Holstein heifers, termed as CN, LC, and HC groups. The supplementation improved physiological indices of respiratory frequency and rectal temperature, increased the concentrations of immunoglobulins and antioxidant capacity-related parameters, and reduced the concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 51 publications
2
14
1
Order By: Relevance
“…Another bacterium worthy of note was bacterium YE57. Although the high-dose CT aqueous extract promoted the relative abundance of bacterium YE57 in the present study (Figure 4), previous studies have found that its abundance was higher in the normal gut than that in the gut treated with high-concentration herbal tea residue [58] and that its abundance was reduced after the intervention with Bacillus licheniformis combined with XOS (xylooligosaccharides) [59]. us, the role of this bacterium in the gut microbiota deserves further study.…”
Section: Discussioncontrasting
confidence: 65%
“…Another bacterium worthy of note was bacterium YE57. Although the high-dose CT aqueous extract promoted the relative abundance of bacterium YE57 in the present study (Figure 4), previous studies have found that its abundance was higher in the normal gut than that in the gut treated with high-concentration herbal tea residue [58] and that its abundance was reduced after the intervention with Bacillus licheniformis combined with XOS (xylooligosaccharides) [59]. us, the role of this bacterium in the gut microbiota deserves further study.…”
Section: Discussioncontrasting
confidence: 65%
“…In ruminant, intestinal flora is influenced by feed ingredients. Xie et al ( 2020 ) fed Holstein heifers by substituting different proportions (0%, 5%, and 10%) of whole corn silage (WCS) with herbal tea residue, finding that the microbial composition of the three treatments was significantly different. Moreover, Sun et al ( 2017 ) fed Holstein cows different percentages of ensiled Moringa oleifera and found a strong correlation between the presence of Akkermansia and Prevotella in total milk yield and milk protein, which indicates that some bacterial groups could be associated with enhanced milk production performance.…”
Section: Introductionmentioning
confidence: 99%
“…HTR is the residual water-insoluble substance produced by herbal tea beverage, which has the potential to be used as feed [22]. Compared with corn silage with a crude protein content of 7-9% [17], in this experiment, HTR contained more crude protein (13.10%).…”
Section: Discussionmentioning
confidence: 85%
“…One study concluded that tea residues could improve the antioxidant capacity of cow plasma [21]. In another study, a fermented herbal residue was fed to Holstein heifers, which effectively promoted the growth and immune performance of cows under heat stress [22].…”
Section: Introductionmentioning
confidence: 99%